Structural Aspect of Formation of a Nanosystem of In/In₄Se₃ (100) - Galiy, P.V.; Mazur, P.; Ciszewski, A.; Nenchuk, T.M.; Yarovets’, I.R.; Dveriy, O.R. (Металлофизика и новейшие технологии, 2018)
Self-assembled indium deposition-induced nanostructures are obtained on the UHV cleaved (100) surface of In₄Se₃ layered semiconductor crystals. The small indium-deposition rates and short deposition times are chosen to study growth orientation and origin of nanostructures observed by scanning tunnelling microscopy (STM) on the (100) surface of In₄Se₃ after indium deposition. The shape of these nanostructures strictly depends on the overstoichiometric indium concentration level in the melt during the crystal growth varying from 3D islands for low concentration to elongated shapes, i.e., nanowires, in the case of highly-indium-doped crystals. High-resolution STM study determines the self-assembled quasi-periodical nanowires’ growth along c-axis of (100)In₄Se₃ substrate. The spatially resolved scanning tunnelling spectroscopy (STS) study revealed metallic nature of the surface of nanostructures grown on the semiconductor substrate. The growth mechanism of indium-deposited nanostructures is considered to be powered by anisotropic striated lattice structure of In₄Se₃ (100) surface with indium nucleiin concentration depending on the degree of overstoichiometric crystal-growth indium subsequently intercalated into the interlayer gap. Самоорганизованные индиевые наноструктуры получены на сверхвысоковакуумной поверхности скалывания (100) полупроводникового слоистого кристалла In₄Se₃. Небольшие скорости и длительности напыления индия использовались с целью исследования ростовой ориентации и природы наноструктур на поверхности (100)In₄Se₃, которые изучались с помощью сканирующей туннельной микроскопии (СТМ). Форма этих наноструктур непосредственно зависит от концентрации сверхстехиометрического индия в расплаве во время роста кристалла, изменяясь от трёхмерных островков при низкой концентрации до линейных форм, т.е. нанопроводов, в случае сильно легированных индием кристаллов. СТМ з высоким разрешением позволяет установить, что квазипериодические нанопровода растут вдоль оси c кристалла In₄Se₃ на поверхности (100). С помощью сканирующей туннельной спектроскопии с пространственным разрешением установлена металлическая природа поверхностных наноструктур на полупроводниковой подкладке. Установлено, что механизм роста напылённых наноструктур обусловлен бороздчатой структурой решётки на поверхности (100) кристалла In₄Se₃ с наличием в ней зародышей индия в концентрации, зависящей от количества сверхстехиометрического ростового индия, который интеркалируется в межслоевую щель. Самоорганізовані індійові наноструктури одержано на надвисоковакуумній поверхні сколювання (100) напівпровідникового шаруватого кристалу In₄Se₃. Невеликі швидкості та тривалості напорошення індію вибиралися з метою дослідження ростової орієнтації та природи наноструктур на поверхні (100)In₄Se₃, які вивчали за допомогою сканувальної тунельної мікроскопії (СТМ). Форма цих наноструктур безпосередньо залежить від концентрації надстехіометричного індію в розтопі під час вирощування кристалу, змінюючись від тривимірних острівців за низької концентрації до лінійних форм, тобто нанодротів, у випадку сильно леґованих індієм кристалів. СТМ з високим розріжненням уможливлює встановити, що квазиперіодичні нанодроти ростуть вздовж осі c кристалу In₄Se₃ на поверхні (100). За допомогою сканувальної тунельної спектроскопії з просторовим розріжненням встановлено металічну природу поверхневих наноструктур на напівпровідниковій підкладинці. Встановлено, що механізм росту напорошених наноструктур зумовлений борознистою структурою ґратниці на поверхні (100) кристалу In₄Se₃ з наявністю у ній зародків індію у концентрації, яка залежить від кількости надстехіометричного ростового індію, що інтеркалюється у міжшарову щілину.